(untitled) (Research, Society and Development, 2022)
Objective: to identify the prevalence of anxious, depressive and stress symptoms in university students. Method: Observational, exploratory and descriptive research carried out in a private educational institution in the east of São Paulo, using Google forms, using the Depression, Anxiety and Stress Scales (DASS-21) and a sociodemographic characterization instrument. Results: They showed a high prevalence of depression, anxiety and stress in university students during the pandemic, with statistical significance for university students in health courses, most of them (72%) health workers, female, white, Catholic, single, without children, employed, with per capita income of 2 to 5 minimum wages and without recreation and leisure activities. Conclusion: Symptoms of stress, anxiety and depression in university students during the COVID -19 pandemic are related to the isolation measures imposed by the government and changes in the daily routine and studies, at different levels and different age groups, in addition to the uncertainties generated, both personally and educationally. The early identification of symptoms, which when carried out at an early stage, can offer a quick treatment in the treatment of these symptoms of stress, anxiety and depression, offering a better quality of life and a success in the training of university students.